Comparison of soil physical quality index based on simple additive SQI and statistically modeled SQI methods for watershed management in Rembangan, Indonesia - Hermiyanto, Bambang; Tika, Sukma Agustin Dyan; Budiman, Subhan Arif; Mandala, Marga; Fitriani, Vivi; Basuki, Basuki (Brawijaya University, 2025)
The physical quality of soil is determined by quantitative measurement tools, which are expressed in the form of soil quality indices. Methods for determining soil quality have been developed, but none have been standardized. This research aimed to determine the results of the soil physical quality index based on two methods, namely 1) simple additive SQI, and 2) statistically modeled SQI, followed by a sensitivity test to determine which method is more sensitive. This research was conducted in the Rembangan Sub-watershed, which comprises five sub-districts: Jelbuk, Arjasa, Patrang, Sukorambi, and Panti, with elevations ranging from 125.91 to 854.67 meters above sea level. Based on the paired t-test results, the soil physical quality index between the two methods was significantly different, with a p-value of 0.002. Meanwhile, the sensitivity test results showed that the statistically modeled method was more sensitive than the simple additive method. Thus, the statistically modeled method is the method that can be used to assess the soil physical quality index for land management guidance. The poor or low-quality class dominates the soil quality class, covering an area of 2,088.43 ha (79.43%). Land management actions based on soil quality are divided into three criteria: 1) “fixed efforts” for low-quality soil, 2) “enhanced efforts” for medium-quality soil, and 3) “maintenance efforts” for good-quality soil.